2017
DOI: 10.1139/cjfas-2016-0325
|View full text |Cite
|
Sign up to set email alerts
|

Larval fish dispersal along an estuarine–ocean gradient

Abstract: The present study investigated the larval fish dispersal along an estuarine–ocean gradient to explore connectivity between ocean and estuaries. During spring 2009, a combined ocean–estuarine survey was conducted along the Lima estuarine salinity gradient and in two transects off the adjacent coast (northwestern Iberian Peninsula), until the 100 m isobaths. Salinity, total particulate matter, particulate organic matter, total dissolved carbon, and dissolved organic carbon reached higher values at the ocean, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…VIF < 10 indicated that the environmental variables were not collinear and were fit for CCA (Graham, 2003;Huang et al, 2017). The importance of the environmental variables was measured by interset correlation coefficients, when the value of interset correlation coefficients ≥| ±0.4| variables were regarded conservatively as biologically important (Rakocinski et al, 1996;Ramos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…VIF < 10 indicated that the environmental variables were not collinear and were fit for CCA (Graham, 2003;Huang et al, 2017). The importance of the environmental variables was measured by interset correlation coefficients, when the value of interset correlation coefficients ≥| ±0.4| variables were regarded conservatively as biologically important (Rakocinski et al, 1996;Ramos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the salinity gradient, water temperature, and inorganic nutrients (especially nitrite, nitrate, and phosphate) were the main variables that affected the larval fish assemblages. Salinity has been widely identified as an important environmental driver of larval fish assemblages (Barletta‐Bergan et al., ; Harris, Cyrus, & Beckley, ; Ooi & Chong, ; Ramos, Paris‐Limouzy, & Angélico, ), controlling the species composition in function of their tolerance to salinity gradients. Water temperature has also been regarded as an important environmental controller, since it is a determinant factor at several stages of a fish life cycle, including gonadal development and spawning (Amorim, Ramos, Elliott, & Bordalo, ; Fincham, Rijnsdorp, & Engelhard, ; Pawson, Pickett, & Witthames, ; Santos et al., ) and growth and survival of ELHS prior to nursery recruitment (Meekan, Carleton, McKinnon, Flynn, & Furnas, ; Vinagre, Santos, Cabral, & Costa, ).…”
Section: Discussionmentioning
confidence: 99%
“…Salinity has been widely identified as an important environmental driver of larval fish assemblages (Barletta-Bergan et al, 2002;Harris, Cyrus, & Beckley, 2001;Ooi & Chong, 2011;Ramos, Paris-Limouzy, & Angélico, 2017), controlling the species composition in function of their tolerance to salinity gradients. Water temperature has also Moreover, it has been shown that nutrient concentrations also have a large influence on the dynamics of ichthyoplankton assemblages (Ramos, Amorim, Elliott, Cabral, & Bordalo, 2012), including the consequent increase in food availability through primary and secondary productivity (Hsieh, Lo, Liu, & Su, 2010;Martin, Cyrus, & Forbes, 1992;Meynecke, Lee, Duke, & Warnken, 2006).…”
Section: Seasonsmentioning
confidence: 99%
“…Larvae usually enter the Lima estuary between February and July (Ramos et al, 2010;Amorim et al, 2016). Direct settlement occurs inside the estuary (Ramos et al, 2010; Amorim et al, 2018), and most likely in the upper section (Ramos et al, 2010), as indicated by the high larval (Ramos et al, 2017) and newly settled flounder abundances found in this area (Ramos et al, 2010;Mendes et al, 2014;Amorim et al, 2016). As in other estuaries (Elliott & Hemingway, 2002), the spatial distribution of flounder in the Lima estuary varies with age (Ramos et al, 2009;Mendes et al, 2014, Amorim et al, 2018.…”
Section: Introductionmentioning
confidence: 97%